Microstructure analysis on spring steels due to fatigue failure - F.N., Ahmad Refngah; S., Abdullah; A., Jalar; L.B., Chua (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.